2009
DOI: 10.5851/kosfa.2009.29.5.545
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ca Equilibrium on the Functional Properties of Cheese: A Review

Abstract: The functional properties of cheese, such as texture and melt, are known to be controlled by several important parameters. Recently, the characteristics of Ca in cheeses, especially the form of Ca (insoluble (INSOL) or soluble) and the shift in Ca equilibrium (i.e., from INSOL to soluble Ca), during aging has received a lot of attention. The INSOL form of Ca, which is present as a structural form in casein, plays a critical role in determining the functional properties of cheese during the early period of ripe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…Regarding the differentiation between soluble and micellar fractions of major minerals, only few studies have characterized such traits, and all dealt with Cheddar cheese (Lucey and Fox, 1993;Hassan et al, 2004). Previous studies reported a decrease of micellar Ca content, and consequently an increase of soluble fraction during ripening (Hassan et al, 2004;Lee and Lee, 2009). Hassan et al (2004) reported total Ca content of 8.33 mg/g and micellar Ca content of 6.44 mg/g at 1 d of ripening, in agreement with results of the current study.…”
Section: Curd Compositionsupporting
confidence: 90%
“…Regarding the differentiation between soluble and micellar fractions of major minerals, only few studies have characterized such traits, and all dealt with Cheddar cheese (Lucey and Fox, 1993;Hassan et al, 2004). Previous studies reported a decrease of micellar Ca content, and consequently an increase of soluble fraction during ripening (Hassan et al, 2004;Lee and Lee, 2009). Hassan et al (2004) reported total Ca content of 8.33 mg/g and micellar Ca content of 6.44 mg/g at 1 d of ripening, in agreement with results of the current study.…”
Section: Curd Compositionsupporting
confidence: 90%
“…Vet. Zootec., v.65, n.2, p.601-609, 2013 of calcium was present inside casein after cheese making (Lucey et al, 2003;Lucey et al, 2005;Chevanan and Muthukumarappan, 2007;Guinee and O'Kennedy, 2009;Lee and Lee, 2009). …”
Section: mentioning
confidence: 99%
“…The pH variations also lead to a shift in calcium equilibrium, and are influenced by factors like composition and pre-acidification of milk, cheese manufacturing pH, acid development during aging, among others. There have been many studies showing that calcium equilibrium affects the rheological properties of cheese (Hassan et al, 2004;Johnson and Lucey, 2006;Lee and Lee, 2009). …”
Section: mentioning
confidence: 99%
“…Camembert cheese is a popular cheese with a short maturation time, high nutritional value and wide consumption (Leclercq‐Perlat et al . 2013; Lee and Bae 2018). Although Camembert cheese has traditionally been produced from cow milk, nowadays, cheese producers are also considering goat and sheep milks to make Camembert cheese (Gebreyowhans et al .…”
Section: Introductionmentioning
confidence: 99%